The Use of Picture Media to Enhance Students’ Writing Ability of Recount Text at MTs N 1 of Bengkulu City, Bengkulu - Dedi Efrizal (At-Ta'lim : Media Informasi Pendidikan Islam, 2019)
Abstract: The Use of Picture Media to Enhance Students’ Writing Ability of Recount Text at MTs N 1 of Bengkulu City, Bengkulu. This study was carried out to improve the students’ writing ability through Pictures media in Second Year Students at Mts N 01 of Bengkulu in the academic year 2018-2019. The subjects of this study have consisted of 42 students. The method used in this study was Classroom Action Research (CAR). The Classroom Action Research design applied in this study was a collaborative classroom action research. It means that the researcher collaborated with the English teacher of Mts N 01 of Bengkulu as an observer and collaborator. The study was carried out in three cycles. Each cycle consisted of three meetings. The data were gathered in this study through field notes, and test. The result of the study showed that there was an improvement in students’ writing ability. Most of the students gradually gained good scores at the end of each cycle. The score of Minimum Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English subject was 70 (seventy). In the cycle, the result of the students' score was poor. In cycle 2 the result of the students' score has some signs of progress, and in the cycle 3, the result of the students' score has improved effectively than action in the cycle before where the mean score of students was in 75 (Good). In addition, there was a positive response from the English Teacher about implementing the action. In conclusion Pictures, media could solve the students’ problems and improve their writing ability.Abstrak: Penggunaan Media Gambar untuk Meningkatkan Kemampuan Menulis Teks Recount Siswa di MTs N 1 Kota Bengkulu, Bengkulu. Penelitian ini dilakukan untuk meningkatkan kemampuan menulis siswa melalui media Pictures pada Siswa Kelas Dua di Mts N 01 Bengkulu pada tahun akademik 2018-2019. Subjek penelitian ini terdiri dari 42 siswa. Metode yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK). Desain Penelitian Tindakan Kelas yang diterapkan dalam penelitian ini adalah penelitian tindakan kelas kolaboratif. Ini berarti bahwa peneliti berkolaborasi dengan guru bahasa Inggris Mts N 01 dari Bengkulu sebagai pengamat dan kolaborator. Penelitian dilakukan dalam tiga siklus. Setiap siklus terdiri dari tiga pertemuan. Data dikumpulkan dalam penelitian ini melalui catatan lapangan, dan tes. Hasil penelitian menunjukkan bahwa ada peningkatan kemampuan menulis siswa. Sebagian besar siswa secara bertahap memperoleh skor bagus di akhir setiap siklus. Skor Kriteria Penguasaan Minimum- Kriteria Ketuntasan Minimal (KKM) mata pelajaran bahasa Inggris adalah 70 (tujuh puluh). Pada siklusnya, hasil nilai siswa buruk. Pada siklus 2 hasil skor siswa memiliki beberapa tanda kemajuan, dan pada siklus 3, hasil skor siswa telah meningkat secara efektif daripada tindakan dalam siklus sebelum di mana skor rata-rata siswa berada di 75 (Baik) . Selain itu, ada tanggapan positif dari Guru Bahasa Inggris tentang penerapan tindakan. Kesimpulannya Pictures, media dapat memecahkan masalah siswa dan meningkatkan kemampuan menulis mereka.